Antinomy Between Legal Certainty and Justice in the Public Housing Savings Program (Tapera) - Heriyanti; Pakpahan , Elvira Fitriyani; Tanjaya, Willy; Siregar, Naek Martahan Hasudungan (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
People's Housing Savings (Tapera) is a government program for home ownership and housing for the community. The implementation of the Tapera program will only be carried out in 2027. However, both in terms of regulation and socialization, it seems rushed and is considered to cause injustice for low-income workers/laborers. The conflict between regulations regarding state efforts to provide housing for the community with mechanisms that are deemed burdensome to the community, on the one hand, causes injustice. So this study aims to find common ground between legal certainty and justice in the Tapera Program. This research is legal research that uses a legislative approach and a conceptual approach to discuss Tapera. Although this program aims to support housing financing, the amount of contributions as regulated in Government Regulation Number 21 of 2024 can cause polemics because it will affect the income of workers who have previously been deducted through Income Tax, BPJS Employment, and BPJS Health membership, and several other taxes or deductions set by the state. So, according to the theory of justice and the General Principles of Good Governance, this Tapera policy can harm justice. People's Housing Savings (Tapera) will be more suitable to be applied only to formal Workers/Laborers (both state and private) because it has a regular wage payment system. Meanwhile, for Independent Workers, it is better if this People's Housing Savings (Tapera) is not an obligation but rather only voluntary, meaning that the wishes of Independent Workers will decide whether to follow the People's Housing Savings (Tapera) program or not.